2002
DOI: 10.1108/02683940210428092
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and organizational citizenship behaviour

Abstract: The purpose of this study was to examine the role of organizational citizenship behaviour as a component of job performance. Participants comprised 41 human-service workers, who completed a job satisfaction questionnaire and were rated for their organizational citizenship, as well as being measured on three discretionary organizational participant behaviours. Job satisfaction correlated significantly with organizational citizenship and participation behaviours (correlations ranged from +0.40 to +0.67). Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 25 publications
7
30
2
5
Order By: Relevance
“…Such results suggest that organizational cultures are stronger in Mexican organizations where employees naturally relate and conform to their respective cultures. Accordingly, and consistent with the previous literature (Alotaibi, 2001;Kuehn & Al-Busaidi, 2002;LePine et al, 2002;Murphy et al, 2002;Waris, 2005;Jena & Goswami, 2013), the average level of job satisfaction was higher in Mexico than in Egypt.…”
Section: Discussionsupporting
confidence: 80%
“…Such results suggest that organizational cultures are stronger in Mexican organizations where employees naturally relate and conform to their respective cultures. Accordingly, and consistent with the previous literature (Alotaibi, 2001;Kuehn & Al-Busaidi, 2002;LePine et al, 2002;Murphy et al, 2002;Waris, 2005;Jena & Goswami, 2013), the average level of job satisfaction was higher in Mexico than in Egypt.…”
Section: Discussionsupporting
confidence: 80%
“…This research results support Murphy, Athanasou, King (2002), Begum (2006), Zeinabadi (2010) that job satisfactions significantly affect on OCB. This finding agrees with study results of Salehi and Gholtash (2011) that there is a positive relationship between job satisfaction and OCB.…”
Section: Effect Of Job Satisfaction On Ocbsupporting
confidence: 85%
“…Satisfied employees likely to speak positively about organization, helping co-workers, and make their performance beyond normal estimates, much more than satisfied employees who more obedient to duty call only, because they want to repeat their positive experiences (Robbins, 2006). Recent research shows that job satisfaction affects OCB (Murphy, Athanasou, King, 2002;Begum, 2006;Zeinabadi, 2010;Salehi and Gholtash, 2011). Nevertheless, still there are difference findings between job satisfaction and OCB.…”
Section: Introductionmentioning
confidence: 99%
“…Podsakoff et al(2006) revealed that employees who are satisfied generally easier to make contributions in excess of the role (Organizational Citizenship behavior) than others, such as the study conducted by Murphy, Athanasou, King (2002), that job satisfaction significantly influence Organizational Citizenship behavior.…”
Section: Introductionmentioning
confidence: 99%